The control and treatment of industrial and municipal stormwater - Moffa, Peter E. (Van Nostrand Reinhold, 1996)
Complete with extended case studies that demonstrate how these methodologies work in the real world, The Control and Treatment of Industrial and Municipal Stormwater is your best choice for ensuring effective stormwater pollution remediation and legal compliance.